Analisa Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan Perusahaan yang Terdaftar di Bursa Efek Indonesia - Oktavia, Mari; Tanujaya, Kennardi (Faculty of Economics, Universitas Internasional Batam, 2019)
This research investigates factors affecting timeliness of annual corporate financial reporting in Indonesia. The sample of the research is a company listed on Indonesia Stock Exchange (BEI) in 2012-2017. Company size, company profitability, company age, leverage, audit committee independence, member audit committee, audit committee experience, auditor type, audit report, auditor rotation and audit opinion used as variable independent. The sample of this research includes 335 company on BEI with 1.675 data. Data obtained from financial statement year ended 2012 until 2017 and panel-regression test to examine the study hypotheses. This reaearch found the average time company needs 120 days for issuing financial report. Variable company age and audit report have significant positive impact on timeliness of financial. Audit committee independent and member audit committee have significant negative impact on timeliness. However variable company size, company profitability, audit committee experience, auditor type, auditor rotation and audit opinion had no effect significant toward timeliness financial report.